Targeting the Nrf2-SLC7A11/GPX4 Pathway to Inhibit Ferroptosis: Mechanism of Yiqi Fumai Formula in Acute Decompensated Heart Failure - Lu Fan; Yunfeng Jia; Yanyang Li; Zhihan Yang; Yiming Zuo; Haomin Zhang; Xuezheng Liu; Shichao Lv (QJM: An International Journal of Medicine, 2026)
Abstract Objective To elucidate the mechanism of Yiqi Fumai Formula (YQFM) in acute decompensated heart failure (ADHF) via the Nrf2/SLC7A11/GPX4 pathway in regulating ferroptosis. Methods Network pharmacology was employed to predict the underlying mechanisms of YQFM in ADHF. Rat models of ADHF were established, incorporating agonists or inhibitors of key ferroptosis pathways. The therapeutic mechanism of Yiqifumai Formula was investigated by assessing cardiac structure/function, myocardial injury biomarkers, lipid peroxidation, iron metabolism, ultrastructural changes, and key ferroptosis pathways. Results Network pharmacology analysis suggested that YQFM might intervene in ADHF by modulating key processes of ferroptosis, including lipid metabolism, inflammatory response, and cell survival. Experimental validation confirmed that YQFM improved cardiac function, reduced myocardial lipid peroxidation, and inhibited cardiomyocyte ferroptosis in rat models. This cardioprotective effect is likely associated with the regulation of the Nrf2/SLC7A11/GPX4 signaling pathway. Conclusion YQFM exerts the cardioprotective effect in ADHF by suppressing ferroptosis through the modulation of the Nrf2-SLC7A11/GPX4 pathway.